The Estimation of Age and Analyses of the Growth Rate Piliostigma thonningii (Schum.) Milne-Redhead in the Guinea Savanna Zone of Nigeria - Isichei, A. O.; Mbaekwe, E. I. (2014)
Estimates of age and analyses of growth rate of Piliostigma thonningii were made by counting rings and measuring ring widths in those plants that formed distinct rings. In the others, with indistinct rings or no rings, the regression method was used to estimate the ages, using known ages and girths to derive a regression equation. There was a high correlation coefficient between age and girth (r = 0.96), less so between age and mean annual growth increment (r = 0.71) and much less so between age and bark thickness (r = 0.54). The estimated mean annual growth increment (cm) for all the tress sampled was 1.07 ± 0.23 (at 95% confidence limit).